Implementasi Program Corporate Social Responsibility (CSR) Perumda Air Minum Surya Sembada Kota Surabaya dalam Mendukung Sustainable Development Goals (SDGs) - Alifani, Mohammad Syafi’udin; Prabawati, Indah; Rahaju, Tjitjik; Al Amin, M Noer Falaq (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This study examines the implementation gap of the Corporate Social Responsibility (CSR) program at Perumda Air Minum Surya Sembada, Surabaya City, in supporting Sustainable Development Goals (SDGs) Goal 4 on Quality Education. Preliminary findings indicate an anomaly between the company's financial capacity and its educational allocation priorities. In 2024, CSR budget realization reached 100.84 percent, totaling Rp 6.99 billion; however, the allocation for educational assistance significantly declined from Rp 983 million in 2022 to Rp 271 million in 2024, following the elimination of the Scholarship Assistance category. This research aims to analyze the implementation of educational CSR using Van Meter and Van Horn’s policy implementation model. A descriptive qualitative approach was employed through in-depth interviews, observations, and document analysis of regulations, annual reports, and budget realization data. The results indicate that the implementation of educational CSR remains suboptimal due to several key factors: policy standards oriented solely toward budget absorption without long-term impact indicators; a resource imbalance characterized by high financial capacity unmatched by the quantity and competence of human resources; limited supporting infrastructure; and closed external communication. Furthermore, the institutional placement of CSR under the public relations function and strong political influence have contributed to a biased and less inclusive pattern of aid distribution. This study concludes that the implementation of educational CSR at Perumda Air Minum Surya Sembada remains administrative in nature and has failed to transform the company's financial potential into sustainable educational empowerment in accordance with the spirit of the SDGs